Nascent polypeptide within the exit tunnel stabilizes the ribosome to counteract risky translation. (20th October 2021) - Chadani, Yuhei; Sugata, Nobuyuki; Niwa, Tatsuya; Ito, Yosuke; Iwasaki, Shintaro; Taguchi, Hideki
Abstract: Continuous translation elongation, irrespective of amino acid sequences, is a prerequisite for living organisms to produce their proteomes. However, nascent polypeptide products bear an inherent risk of elongation abortion. For example, negatively charged sequences with occasional intermittent prolines, termed intrinsic ribosome destabilization (IRD) sequences, weaken the translating ribosomal complex, causing certain nascent chain sequences to prematurely terminate translation. Here, we show that most potential IRD sequences in the middle of open reading frames remain cryptic and do not interrupt translation, due to two features of the nascent polypeptide. Firstly, the nascent polypeptide itself spans the exit tunnel, and secondly, its bulky amino acid residues occupy the tunnel entrance region, thereby serving as a bridge and protecting the large and small ribosomal subunits from dissociation. Thus, nascent polypeptide products have an inbuilt ability to ensure elongation continuity. Synopsis: Acidic‐rich amino acid sequences destabilize the translating ribosome, stochastically inducing elongation abortion. This study unveils a positive feedback system mediated by the nascent chain within the ribosomal tunnel, which ensures elongation continuity by stabilizing the ribosome. Translation of acidic or proline‐intermitted intrinsic ribosome destabilization (IRD) sequences favors premature elongation cessation. Nascent peptide within the ribosomal exit tunnel helps to ensure translation continuity by counteracting IRD. IRD‐counteracting mechanisms include the exit tunnel‐spanning nascent polypeptide and its bulky amino acid residues that occupy the tunnel entrance region. Selection for length and bulkiness in nascent chains to minimize the risk of nonproductive translation discontinuation affects amino acid distribution throughout the proteome. Abstract : Translation elongation continuity in spite of intrinsic ribosome destabilization sequences is ensured by interaction of the nascent polypeptide with the exit tunnel.